2010
DOI: 10.1080/13854046.2010.506199
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Clinical Picture of Patients with Complicated vs Uncomplicated Mild Traumatic Brain Injury

Abstract: To compare the acute clinical profile of patients with uncomplicated vs complicated mild TBI (MTBI), socio-demographic and medical history variables were gathered for 176 patients diagnosed with MTBI and with (complicated, N = 45) or without (uncomplicated, N = 131) positive findings on cerebral imaging. Neurological examination, neuropsychological assessment and self-evaluation of post-concussive symptoms were done at 2 weeks post trauma. Patients with complicated MTBI were more likely to show auditory and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…), and the intervals at which outcomes were measured, ranging from 1 week to 1 year. Several prospective 911 and retrospective 4 studies have reported no or very small differences between cmTBI and mTBI in neuropsychological test performance, return to work rates, or global outcomes. Others have found worse outcomes for cmTBI on global outcome measures 12 or neuropsychological tests.…”
Section: Introductionmentioning
confidence: 99%
“…), and the intervals at which outcomes were measured, ranging from 1 week to 1 year. Several prospective 911 and retrospective 4 studies have reported no or very small differences between cmTBI and mTBI in neuropsychological test performance, return to work rates, or global outcomes. Others have found worse outcomes for cmTBI on global outcome measures 12 or neuropsychological tests.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a minority of survivors develops PTSD, and resilience factors help in resistance to the development of PTSD (deRoon-Cassini et al 2010). For example, in their study, anger reactions and difficulties with coping selfefficacy were associated with poorer trajectories in a sample of participants requiring level 1 trauma care, whereas education served a protective factor.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 94%
“…De Guise et al (2010) examined over 2 weeks the clinical profile of patients with complicated (e.g., positive cerebral imaging) and uncomplicated mTBI, including for neurological signs, neuropsychological performance, and self-reported post-concussive symptoms. The latter group reported more post-concussive symptoms, and the two groups appeared equally affected otherwise at the neuropsychological level, with many in both groups returning to work after 2 months on average.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…The results indicated that 43.9%, 62.5% and 51.2% of participants expected greater symptom disturbance than the clinical cut-score in the control, concussion and mTBI groups respectively; however, no effect of terminology was found using this criterion, 2 (2) ¼ 2.85, p ¼ 0.261 (2-tailed). Using the PCL-C cut-score of 50 [30], only 14.6%, 20.0% and 19.5% of participants expected greater PTSD symptom disturbance than the clinical cut-off in the control, concussion and mTBI groups, respectively, and there was no significant effect of terminology, 2 …”
Section: Effect Of Diagnostic Terminology On Outcomesmentioning
confidence: 98%
“…Mild traumatic brain injury (mTBI) is a common neurological condition that can result in a significant financial and health burden to individuals and society [1,2]. MTBIs sustained in a sporting context are of particular concern given the increased risk of sustaining such an injury during play [3].…”
Section: Introductionmentioning
confidence: 99%